Reading social studies - Beers, G. Kylene (Holt, Rinehart and Winston, a Harcourt Education Company, 2007)
Learning and thinking and reading, discovering that connection in the social studies classroom / K. Beers -- Reading skills: Setting a purpose; Making predictions; Identifying main ideas and details; Summarizing; Making inferences; Sequencing; Identifying cause and effect; Comparing and contrasting; Identify problems and solutions; Drawing conclusions; Making generalizations -- Think-alouds: How to use think-alouds with your students; Types of think-aloud comments; Reading American history; Reading world history; Reading geography; Reading civics -- Graphic organizers: How to use graphic organizers; Graphic organizers -- Answer key.